PENGEMBANGAN MEDIA INTERAKTIF BERBASIS PENDEKATAN KONSTRUKTIVIS PADA MATERI BANGUN RUANG SISI DATAR DI KELAS VIII SMP/MTs - Edo Hemat Perdana (Departemen Matematika, 2022)
Interactive media is a means of supporting learning that can increase interest and motivation to learn and affect the psychology of students so that learning becomes easier. Interactive media help students understand the learning material and develop their critical thinking skills. This study intends to develop an interactive learning media based on constructivists that is valid and practical on flat-sided building materials in class VIII SMP / MTs. This type of research is development using the Plomp model. The plomp model is composed of Preliminary, Prototyping and Assessment Phase. In the introduction, needs analysis, student analysis, curriculum analysis, and concept analysis were carried out. The prototyping stage is in the form of designing interactive learning media. In prototype 1, self evaluation and expert review are carried out. Expert review was conducted to see the validity of the developed interactive learning media. In prototype 2, a one-to-one evaluation trial was carried out by testing interactive media with three students. The result of the research shows that constructivist based interactive media on the flat side space building material has a validity level in the very valid category. Interactive media has a practicality level in the very practical category. Based on these results, it can be concluded that the interactive media produced are valid and practical. Keywordss __ InteractivemMedia,aConstructivism,PPlomp